2022
DOI: 10.3390/ijerph19010491
|View full text |Cite
|
Sign up to set email alerts
|

The Complicated Relationship between Dieting, Dietary Restraint, Caloric Restriction, and Eating Disorders: Is a Shift in Public Health Messaging Warranted?

Abstract: The origins of theories specifying dietary restraint as a cause of eating disorders can be traced to the 1970s. This paper will present an overview of the origins of dietary restraint theories and a brief historical review of evidence will be summarized. Recent research will be presented, including the results from the CALERIE Phase 1 study, as well as CALERIE Phase 2, which were NIH-sponsored randomized controlled trials. CALERIE 2 provided a test of the effect of two years of caloric restriction (CR) on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 105 publications
(142 reference statements)
0
14
0
4
Order By: Relevance
“…Hence these two components of behavioural weight management are thought to tie into the Dual Pathway sequence to promote disordered eating behaviours (44) . This is a contentious theory, with intervention studies of restricted energy intake for up to two years in individuals without obesity (such as the CALERIE trials (84; 85) ), demonstrating increases in dietary restraint without increases in binge eating or eating disorders (86) . Indeed, this leads to the conceptualisation of dietary restraint as a successful self regulation strategy.…”
Section: Individual Variation In Responses To Weight Management Inter...mentioning
confidence: 99%
“…Hence these two components of behavioural weight management are thought to tie into the Dual Pathway sequence to promote disordered eating behaviours (44) . This is a contentious theory, with intervention studies of restricted energy intake for up to two years in individuals without obesity (such as the CALERIE trials (84; 85) ), demonstrating increases in dietary restraint without increases in binge eating or eating disorders (86) . Indeed, this leads to the conceptualisation of dietary restraint as a successful self regulation strategy.…”
Section: Individual Variation In Responses To Weight Management Inter...mentioning
confidence: 99%
“…In a cohort study of young women dieting, only 3.5% developed an ED of clinical severity during the 2-year follow-up [ 63 ]. A recent review found no experimental support for the DR theories of EDs, suggesting that DR may activate vulnerability factors leading to ED symptoms but only among those already vulnerable [ 64 ]. As previously stated, DR may be a consequence of weight gain and the perception of overeating.…”
Section: Ultra-processed Food Addiction and Dietary Restraintmentioning
confidence: 99%
“…Divergent views in the field may arise from a failure to separate advocacy from evidence, as well as training/discipline bias. Efforts to find a common ground between the prevention of obesity and EDs are greatly needed [ 64 ]. But given that UPFA is not synonymous with obesity, it is imperative that researchers and clinicians understand the potential relationship between weight stigma and UPFA independent of BMI.…”
Section: Ultra-processed Food Addiction and Body Image Disturbancementioning
confidence: 99%
“…Caloric restriction (CR), as a component of some dietary interventions, has been studied extensively in animals and humans for its effect on longevity and other health outcomes [ 7 9 ]. In humans, however, the overall role of CR in physical and mental health is complex with context being important [ 10 ]. For example, CR may effectively reduce body weight and improve metabolic outcomes among those with and without obesity [ 11 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, cross-sectional studies have linked chronic self-reported dieting to disordered eating [ 14 ], reduced self-esteem and higher depression [ 15 ], body dissatisfaction [ 16 ], and increased concern with body shape [ 17 19 ] among some populations. Indeed, factors such as obesity, the presence of disordered eating and other clinical conditions, or their interactions may inform whether or not CR is appropriate [ 10 ].…”
Section: Introductionmentioning
confidence: 99%